Pencantuman Klausula Proteksi Diri Oleh Notaris Dalam Pembuatan Akta Notaris: Perspektif Undang-Undang Jabatan Notaris - Putrawan, I Putu Reinaldy; Sarjana, I Made (Acta Comitas; Vol 8 No 03 (2023)DO - 10.24843/AC.2023.v08.i03.p5, 2023)
The purpose of this study is to determine the legality of notarial deeds with the inclusion of self-protection clauses by Notary and related to the authenticity of notarial deeds that include self-protection clauses in relation to the exercise of authority to make authentic deeds. This study uses normative legal research method with statutory, factual, analytical and conceptual approaches. The research results show that the use of the self-protection clause by Notary is prohibited in the Notary Public Law because it places Notary as a party in the deed. Notaries can still be held liable for the losses of the parties as a result of the implementation of their position in terms of making deeds, including the clause, which actually the Notary cannot take refuge in the clause Authenticity of the deed with the inclusion of the clause will have legal implications that make the deed degraded or lose its evidentiary power to become a deed under the hand.